1995
DOI: 10.1111/j.1365-2621.1995.tb09805.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Maceration of Vegetables with Protopectinases

Abstract: Nippon Eiyo Shokuryo Gakkaishi (J. Jpn. Soc. Nutr. Food Sci.) 36, 219~224 (1983) Relationship between maceration and pectic-substance release of vegetable tissues when they were boiled in different pH solutions was studied. The results obtained were as follows : 1. Vegetable tissues were kept firm when cooked at pH 4. They were rapidly softened by cooking either above pH 5 or below pH 3. By prolonged cooking carrot, potato and Japanese radish were considerably macerated even at pH 4. Maceration of lotus and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
11

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
0
20
0
11
Order By: Relevance
“…In this study, we observed significant differences in pectinase, carboxymethyl cellulase, and proteinase activities among the different B. sorokiniana isolates; such enzymes are often associated with initial phases of host penetration. Polysaccharide-degrading enzymes, such as carboxymethyl cellulase and pectin lyase, are commonly involved in the degradation of plant cell walls (NAKAMURA et al 1995, SANCHEZ-ROMERO et al 1998. Indeed, cellulases from B. sorokiniana effectively hydrolyse cellulosic materials, including wheat tissues (GEIMBA et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed significant differences in pectinase, carboxymethyl cellulase, and proteinase activities among the different B. sorokiniana isolates; such enzymes are often associated with initial phases of host penetration. Polysaccharide-degrading enzymes, such as carboxymethyl cellulase and pectin lyase, are commonly involved in the degradation of plant cell walls (NAKAMURA et al 1995, SANCHEZ-ROMERO et al 1998. Indeed, cellulases from B. sorokiniana effectively hydrolyse cellulosic materials, including wheat tissues (GEIMBA et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Pectinolytic enzymes are widely used in the food and beverage industries to clarify fruit juices and wines, to improve cloud stability in fruit and vegetable nectars, and to increase the protein content of fruit juices. The ability to degrade pectins could be used as an alternative method of pectin extraction from by-products of the fruit industry and also to macerate vegetable tissues in order to produce single-cell foods [18].…”
Section: Introductionmentioning
confidence: 99%
“…The name PPase for this enzyme was proposed by Sakai et al [1] to differentiate it from the classical polygalacturonases without pectin releasing activity. PPase-SE is highly efficient for enzymatic extraction of pectin from citrus peel [3] and for maceration of potato tissues to obtain single-cell foods [4].…”
Section: Introductionmentioning
confidence: 99%